Analisis Perbandingan Manajemen Bandwidth Quality of Service Dengan Menggunakan Metode Simple Queue Dan Queue Tree Pada Telkom University Landmark Tower - Rahman, Ilham Auliya; Kurniawan, MT.; Saedudin, Rd. Rohmat (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
The advancement of the internet impacts the flow of information circulating among internet users, which increases yearly. Telkom University has a TULT building that provides internet access services to all internet users in that building. However, the internet service in that building still needs to be improved as internet users still experience internet problems such as sudden disconnection, slow connection, and unstable connection. Therefore, bandwidth management is needed to improve the quality of internet services in the building. There are several methods to perform bandwidth management, but this study uses Simple Queue and Queue Tree methods. The selection of the Simple Queue and Queue Tree methods in this study is due to the difference in configuration between the two. Bandwidth management simulation uses 4 Mikrotik routers and six laptops as clients. The simulation is conducted for 1 hour via video streaming and online meetings with each client. During the simulation, traffic data is also captured using the Wireshark application. Then, from that Wireshark capture, Throughput, Packet Loss, Delay, and Jitter from the Simple Queue and Queue Tree methods, are analyzed. This research concludes that using the Queue Tree method is more appropriate because it has a packet loss value below 1% with the internet network characteristics of the TULT building, which has a packet loss value above 7.80%. Besides that, the working method of the Queue Tree will be beneficial when the TULT building internet network is experiencing peak traffic.